The Impact of Extroversion and Introversion Personality Types on EFL Learners’ Preferences in Publishing Research Papers - Ririt Rachma Miranti; Putri Aulia Swastika; Muhammad Rauuf Oktavian Nur (Jurnal Studi Guru dan Pembelajaran, 2020)
Personality may affect our way to learn. Based on the important role of different personality types in the foreign language learning process and in mastering a foreign language, this study aims at investigating through the impact of extroversion and introversion personality impact on English as Foreign Language learners’ preferences in publishing research papers. Fifty students are taking part in this study. Those participants are the fifth-semester students of Universitas Tidar who take Teaching English as a Foreign Language class. They have many papers from any lecture. They can produce more than three research papers in a year. Publishing their papers still become interesting topics for them. The researcher uses descriptive qualitative method to get the result. By giving a questionnaire to all of the participants to find out their personality types and then asking about their preferences in publishing research papers. Based on the findings, the researcher gets the main result, there are more extroverts of English as Foreign Language Learners than the introvert one. They could give wide perspectives about publishing their papers. Their perspectives on their preferences depend on any reason that supports the result.